TO ANALYZE THE TB-PCR POSITIVITY RATE USING REAL-TIME PCR FOR EARLY DETECTION OF TUBERCULOSIS - SAWANT, DEEPAK; CD, LOKHANDE; RK, SHARMA; RA, CHOUGULE (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Tuberculosis is one of the leading causes of death worldwide. It is present in all the countries and among all age groups and also seen in both the genders. In investigating the early stage, identification, and rapid detection of tuberculosis, the PCR method (polymerase chain reaction) is one of the fast, safest, and reproducible new approaches. It covers all advantages such as the use of closed systems, reduced risk of carryover contamination, improved sensitivity and reproducibility, reduced turnaround time wide dynamic range of target detection, and feasibility for quantitation making it easy and reliable for the early detection of Mycobacterium tuberculosis. Methods: All samples used for the study are confirmed by conventional microscopic observation using acid-fast staining using ZN STAIN. The pulmonary sputum samples are obtained from clinical and radiological evidence of tuberculosis and these samples are selected for DNA extraction. Discussion: As per the statistical analysis using SPSS 22 version, it is found that the TB positivity rate (is 29.75%). Out of 119 positive patients (Male: 60.5% and Female: 39.5%). The average and standard deviation for CT values are 23.6 and 2.9, respectively. The 95% confidence interval of CT values for specimens is (22.7, 24.5). Average and standard deviation for CT values are equal in male patients and female patients. Age group-wise average and standard deviation for CT values are nearly equal. Results: The percentage of 3+ AFB positive grades having CT values between 20 and 24 is more than all other combinations of AFB positive grades and CT values. The average and standard deviation for CT values are 23.6 and 2.9, respectively. The 95% confidence interval of CT values for specimens is (22.7, 24.5). The average and standard deviation for CT values are equal in male patients and female patients. Conclusion: A significant improvement in specificity with high accuracy was achieved by a real-time PCR assay. Real-time PCR tests prove both a high degree of sensitivity in the upper respiratory sputum samples and for the early detection of the TB infection. The MTB real-time PCR test suitably identified the majority of the AFB positive and bacterial culture confirms TB.